Leveraging mechanisms governing pancreatic tumorigenesis to reduce pancreatic cancer mortality - Donahue, Timothy R. (Trends Endocrinol Metab, 2016)
Pancreatic ductal adenocarcinoma (PDA) is a devastating malignancy with limited and modest clinical treatments. High throughput technologies and accurate disease models now provide a comprehensive picture of the diverse molecular signaling pathways and cellular processes governing PDA tumorigenesis. Central among these is oncogenic KRAS, a mediator of cellular plasticity, metabolic reprogramming, and inflammatory and paracrine signaling required for tumor development and maintenance. Biological aggressiveness is further conferred by a highly fibrotic and immunosuppressive PDA microenvironment that also acts as a barrier to effective drug delivery. The regulation of these mechanisms and their implications for early cancer detection, chemoprevention and therapy are discussed.